PENGARUH STATUS SOSIAL EKONOMI ORANG TUA TERHADAP MOTIVASI BELAJAR KELAS X SMAN 1 SEJANGKUNG - Kadarwati, Ilsya; Rustiyarso, Rustiyarso; Al Hidayah, Riama (Jurnal Pendidikan dan Pembelajaran Khatulistiwa, 2019)
AbstractThis study aims to determine the effect of parents' socioeconomic status on learning motivation in class X students of SMA Negeri 1 Sejangkung. The method used is descriptive method and the form of research is a form of relationship study research. The population in this study were 259 and the sample was 51 (random) students of SMA Negeri 1 Sejangkung. This study uses a quantitative approach. Data collection techniques used are indirect communication techniques and data collection tools with a questionnaire. While the data analysis technique uses the percentage formula and uses SPSS version 24. Based on the results of this study the relationship of parents' socioeconomic status to learning motivation in class X students of SMA Negeri 1 Sejangkung with rcount = 0.800 is in the